Investigation of the Moisture Content Effect on Dielectric Parameters in Peach and Quince Leaves - Başyiğit, Bahadır (Fırat University, 2020)
Today, in the agricultural sector, the use of remote sensing and automation systems is increased to increase the yield and quality of the product. One of the main determinant parameters in the technologies used in microwave heating/drying and remote monitoring/control an application is the dielectric properties of plants. Therefore, it is important to determine the dielectric characteristics of plant materials for proper operation of the systems to be used in these applications. In this study, dielectric parameters of the peach and quince leaves produced in Isparta region are measured by Waveguide Transmission Line Method. Measurements are conducted between 3.30-4.90 GHz (for WR229 waveguide) and the dielectric characteristics of the leaves are examined depending on the moisture content and frequency. A new model with a curve fitting method based on frequency and moisture content (MC) is proposed used dielectric measurement data of peach leaves. This model is compared with the dielectric measurement results of quince leaves which belong to the same family with peach type to see the accuracy of the proposed model is tested. To obtain the performance of the model, the coefficient of determination R2 and Mean Square Root of Errors (RMSE) are obtained as 0.995 and 0.755, respectively.

Günümüzde tarım sektöründe, ürünün verim ve kalitesini artırmak için uzaktan algılama ve otomasyon sistemlerinin kullanımı artmaktadır. Mikrodalga ısıtma/kurutma ve uzaktan izleme/kontrol uygulamalarında kullanılan teknolojilerde temel belirleyici parametrelerden biri, bitkilerin dielektrik özellikleridir. Bu nedenle, bu uygulamalarda kullanılacak sistemlerin doğru çalışması için bitkisel malzemelerin dielektrik karakteristiklerinin belirlenmesi önem arz eder. Bu çalışmada Isparta bölgesinde yoğun olarak üretilen şeftali ve ayva ağaçlarının yapraklarına ait dielektrik parametreler Dalga Kılavuzu İletim Hattı yöntemiyle ölçülmüştür. Ölçümler 3,30-4,90 GHz arasında (WR229 dalga kılavuzu için) yapılmış ve yaprakların dielektrik karakteristikleri nem içeriği ve frekansa bağlı olarak incelenmiştir. Şeftali yapraklarının dielektrik ölçüm verileri kullanarak frekans ve nem içeriğine (Nİ) bağlı, eğri uydurma yöntemiyle yeni bir model önerilmiştir. Bu model, şeftali türüyle aynı aileden olan ayva yaprağının dielektrik ölçüm sonuçlarıyla karşılaştırılarak önerilen modelin doğruluğu test edilmiştir. Modelin performansını görmek için regresyon katsayısı R2 ve Hataların Ortalama Kare Kökü (RMSE) değerleri sırasıyla 0,995 ve 0,755 olarak elde edilmiştir.
Şeftali ve Ayva Yapraklarında Nem Miktarının Dielektrik Parametreleri Üzerindeki Etkisinin İncelenmesi